Gene expression comparison of flow diversion and coiling in an experimental aneurysm model. (20th October 2014) - Puffer, Cole; Dai, Daying; Ding, Yong-Hong; Cebral, Juan; Kallmes, David; Kadirvel, Ramanathan
Abstract : Background and purpose: Mechanisms of both healing and complications, including spontaneous aneurysm rupture, remain unclear following flow diverter treatment. The aim of this study was to compare gene expression of various key molecules involved in the healing of aneurysms, between aneurysms treated with microcoils and flow diverters. Methods: Saccular aneurysms were created in rabbits. Aneurysms were treated with coils (n=6) or flow diverters (n=6). Aneurysms were harvested at 4 weeks following treatment and used for gene expression and zymography experiments. Genes with a fold change of 1.2 or more were considered upregulated whereas those with a fold change of 0.8 or less were considered downregulated. Results: All coil embolized aneurysms were completely occluded at follow-up. Two aneurysms were occluded and the remaining four samples were incompletely occluded in the flow diverter treated group. The following genes were expressed at lower levels in the flow diverter group compared with the coiled aneurysm group: proteinases (matrix metalloproteinases 2 and 9), cellular markers (endothelial nitric oxide synthase and smooth muscle actin), and structural proteins (collagens and fibronectin). Genes related to inflammation (tumor necrosis factor α and monocyte chemoattractant protein 1) were upregulated in flow diverter treated aneurysms compared with coil embolized aneurysms. Notably, the enzymatic activity of active matrix metalloproteinase 9 was high in aneurysms treated with flow diverters. Conclusions: Our findings may provide improved understanding of rupture risk and healing following aneurysm treatment and inform development of therapies aimed at lowering rupture risk and accelerating healing.